Effect of Aging Time and Thickness on Low‐Temperature Degradation of Dental Zirconia. Issue 1 (20th July 2018) - Zhuang, Yongxiang; Zhu, Ziyuan; Jiao, Ting; Sun, Jian
Abstract: Purpose: To evaluate the influence of specimen thickness and low‐temperature degradation (LTD) on yttrium‐stabilized tetragonal zirconia polycrystals (Y‐TZP). Materials and Methods: Thin discs of Y‐TZP from four manufacturers were sintered according to each manufacturer's recommendations, cut into 23 mm (length) × 4 mm (width) × 0.8 mm/1.5 mm (thickness) specimens, artificially aged under standard autoclave sterilization conditions (34°C at 0.2 MPa for 10 and 20 hours), and finally ground and polished. Tetragonal to monoclinic transformation was confirmed by X‐ray diffraction (XRD) analysis. Flexural strength was measured by 3‐point bending tests and Vickers hardness measurements. Fracture surfaces were examined by scanning electron microscopy (SEM). Results: SEM investigation revealed that with increasing aging time, the surface defects and grain size increased, particularly in the 20‐hour group. Compared with the 1.5 mm group, the 0.8 mm group showed more significant defects, irrespective of aging time. The flexural strengths of Y‐TZP materials decreased with a decrease in the thickness. Moreover, LTD of Y‐TZP can cause significant tetragonal to monoclinic transformation, which also results in a statistically significant decrease in the flexural strength. Conclusion: A thinner Y‐TZP specimen was likely to present surface defects and microcracks after aging. In addition, the flexural strengths decreased with a decrease in the thickness, a notable fact for further studies.